Cross-Cultural Study of the Attitudes of Russian and Chinese Consumers Toward Electric Vehicles - Zhao, Fei (Frontiers in Psychology, 2022)
The article presents the results of a study of psychological factors of consumer loyalty concerning electric vehicles. An electric scooter was used as an example of an electric vehicle. The study involved a total of 165 people in China and 150 people in Russia. The study aimed to compare the psychological characteristics of Russian and Chinese consumers based on their attitudes towards an innovative product such as the electric scooter. Hypotheses: 1) The identity of Russian and Chinese consumers and the perceived individuality of the product (electric scooter) differ significantly; 2) The proximity of the consumer's identity and the image of the product (electric scooter) enhances the positive attitude towards the product; 3) Risk strategies of consumer behavior of Chinese and Russians differ. Methods: The questionnaire included the scales: 1) "Measuring brand personality" by J. Aaker, 2) "Measuring consumer identity” elaborated by Morozova and Antononva, 3) The risk behavior scale by Vasilenko, Tkachenko. Results: 1) The first hypothesis was confirmed: there were revealed differences in the consumer behavior of the respondents of these two groups concerning in their self-perception, as well as in the perception of electric scooters. The Russians perceive an electric scooter as energetic, young, extravagant, modern, and unusual; the Chinese are down-to-earth, family-oriented, real. 2) The hypothesis that the correlation of the consumer's identity and the individuality of the product is one of the psychological factors that determine the consumer's loyalty to a product is also confirmed. 3) The Chinese consumers’ identity is more close to the product individuality and their loyalty to the product is higher. 4) Risk strategies of consumer behavior of Chinese and Russians significantly differ in terms of satisfaction with choosing of vehicle, the frequency of its use, and the importance of family approval of the choice of vehicle. The results can be used in the marketing strategy development. From the scientifical perspective, these results contribute to an understanding of the consumer loyalty mechanisms associated with consumer identity.